Assessment of Infection Prevention and Control Minimum Requirements for Primary Health Care Facilities, Ain Zara, Libya - Rehab Jerbi; Miluda Elhamadi (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. Infection prevention and control (IPC) is a critical component of healthcare delivery, ensuring patient safety and reducing the transmission of healthcare-associated infections (HAIs). Primary healthcare facilities play a vital role in providing essential healthcare services to communities. Therefore, assessing the IPC practices in these settings is crucial for ensuring the provision of safe and effective care. This study aimed to assess the IPC minimum requirements for primary healthcare facilities located in Ain Zara municipality, Tripoli. Methods. A descriptive cross-sectional study was conducted on September 2023 at fourteen primary health care facilities in Ain Zara municipality. The WHO assessment tool on IPC minimum requirements for primary health care facilities was used to collect the data and analysis was done by using SPSS. Results. IPC core components score of Ain Zara primary healthcare facilities range from 10 to 22 out of 26 (38.46% -84.62%) which means inadequate level of IPC promotion and practice. Conclusions. Improvement and development of an action plan is required for Ain Zara primary healthcare facilities. Equitable attention is required on all eight components of IPC in all facilities.